Jedi trial - Sherman, David; Cragg, Dan. (New York : Del Rey/Ballantine Books, 2005)
Pors Tonith, minion of Count Dooku, lays siege to the planet Praesitlyn, home of the intergalactic communications center that is key to the Republic's survival in the Clone Wars. Jedi Master Nejaa Halcyon, Anakin Skywalker, and a small contingent of clone soldiers defend the planet in a do-or-die mission.
"A Clone Wars novel."
"Lucas Books.
Keywords: Life on other planets -- Fiction; Vader, Darth (Fictitious character) -- Fiction; Science fiction; Star Wars fiction